2009
DOI: 10.1124/mol.109.054817
|View full text |Cite
|
Sign up to set email alerts
|

PAQRs: A Counteracting Force to Ceramides?: Figure 1.

Abstract: In recent years, sphingolipids have garnered increasing attention for their roles in modulating intracellular signaling events. Circulating factors associated with obesity promote excess accumulation of ceramide or glucosylceramide derivatives, which impair insulin action in peripheral tissues. In this issue, Villa et al. (p. 866) provide evidence that, in yeast, the progestin and adipoQ receptor superfamily of receptors mediate their effects via a novel ceramidase activity, generating sphingoid base as a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Adiponectin exerts its effects by binding to two receptors, AdipoR1 and AdipoR2., which belong to the progesterone and adiponectin Q receptor (PAQR) family. [68] Because some PAQR receptors enhance ceramidase activity, Holland et al tested whether AdipoR1 and AdipoR2 might mediate the ability of adiponectin to lower ceramide. Adiponectin increased ceramidase activity in mouse embryonic fibroblasts (MEFs) with intact adiponectin receptors but failed to do so in MEFs in which both isoforms were deleted.…”
Section: Cross-talk Between Adiponectin and Ceramidementioning
confidence: 99%
“…Adiponectin exerts its effects by binding to two receptors, AdipoR1 and AdipoR2., which belong to the progesterone and adiponectin Q receptor (PAQR) family. [68] Because some PAQR receptors enhance ceramidase activity, Holland et al tested whether AdipoR1 and AdipoR2 might mediate the ability of adiponectin to lower ceramide. Adiponectin increased ceramidase activity in mouse embryonic fibroblasts (MEFs) with intact adiponectin receptors but failed to do so in MEFs in which both isoforms were deleted.…”
Section: Cross-talk Between Adiponectin and Ceramidementioning
confidence: 99%
“…AdipoR1 and AdipoR2 enhance ceramidase activity [164]. An accumulation of ceramide promotes an array of activities related to metabolic diseases, often in direct opposition to adiponectin [165]. The activity of ceramidase converts ceramide to S1P, a potent inducer of proliferation and inhibitor of apoptosis [166].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin research took a significant step forward when it was found that adiponectin receptors contain inherent ceramidase activity, degrading ceramide and forming sphingosine and S1P [45,111]. Indeed, it appears that many of adiponectin's beneficial effects are mediated by accumulation of S1P, including the activation of AMPK [44].…”
Section: Adiponectinmentioning
confidence: 99%